Ethnobotany and conservation of Kasturi (Mangifera casturi Koesterm.) by Banjar Tribe in South Kalimantan, Indonesia - GUNAWAN GUNAWAN; MUHAMAT MUHAMAT; MAGHFIROH MAGHFIROH (Society for Indonesian Biodiversity, 2024)
Abstract. Gunawan, Muhamat, Maghfiroh. 2024. Ethnobotany and conservation of Kasturi (Mangifera casturi Koesterm.) by Banjar Tribe in South Kalimantan, Indonesia. Biodiversitas 25: 1420-1426. Kasturi (Mangifera casturi Koesterm.) is a local fruit and has become the identity flora of South Kalimantan. This study aimed to investigate the knowledge of the Banjar tribe community and formulate a conservation strategy for Kasturi as the identity flora of South Kalimantan. Data on ethnobotanical knowledge were collected through interview technique. There were two types of informant: Key informants and additional informants. Key informants were selected through snowball sampling technique while additional informants were selected a combination snowball sampling and purposive sampling technique. The informants in this study have different background: Sex, age, job, marital status, and educational levels. The informants were grouped based on their age: teenagers (10-18 years), adults (19-59 years), and elders (60+ years). Data were analyzed using the formula of Kasturi plant parts usage (F), Fidelity Level (FL). All data collected were analyzed descriptively and presented in tables or diagrams. The Banjar tribe used M. casturi as source of food (63%), building material (32%), and drugs (5%). The parts of the Kasturi plant that are widely used by the community are fruit, which is 58%, stems are 37%, and leaves are 5%. The values of F (the frequency of parts of Kasturi used) observed from the economic use and health aspects of Kasturi include: building materials, food sources, economic and medicine. The value of F for economic use are 12.78%-100% and the value F for health aspect are 5%. The result of Fidelity Level (FL) analysis proves that all age groups had 100% of FL in utilizing fruits of Kasturi as local food source. The FL of Kasturi bark used is described as follows: 51.34% among teenagers, 89.54% among adults, 87.23% among elder as building materials. The FL value of leaf described 5% among elder. Most of the Banjar tribe get Kasturi fruit from plants that grow wild in their yards (42%) and only 6% have planted. The research indicated that M. casturi had high utility value for Banjar tribe. All parts of the plant (fruits, bark, and leaves) were exploited for economic and health. Conservation of Kasturi can be performed by: (i) Network development and collaboration for conservation efforts, (ii) Ex-situ conservation, (iii) Intensification of socialization and publication of Kasturi's uses, and (iv) Environmental education. The result of the study can be used for management conservation of M. casturi to ensure the availability in the future.